Sampling as a resource-rational constraint. (11th March 2020) - Sanborn, Adam N.; Zhu, Jianqiao; Spicer, Jake; Chater, Nick
Abstract: Resource rationality is useful for choosing between models with the same cognitive constraints but cannot settle fundamental disagreements about what those constraints are. We argue that sampling is an especially compelling constraint, as optimizing accumulation of evidence or hypotheses minimizes the cost of time, and there are well-established models for doing so which have had tremendous success explaining human behavior.